SiO2-confined silicon/carbon nanofiber composites as an anode for lithium-ion batteries - Dirican, Mahmut; Lu, Yao; Fu, Kun; Kizil, Huseyin; Zhang, Xiangwu (Royal Society of Chemistry (RSC), 2015)
A nanoscale silica coating of silicon/carbon nanofibers enabled stable solid electrolyte interphase formation on an electrode surface and improved cycling performance.